A Journey from Wrocław to San Francisco: Memoir of А Bookstore Owner. (3rd April 2021) - Ahrens-Puławski, Veronica; Giullian, Jon C.
ABSTRACT: This memoir tells the story of how Veronica Ahrens-Puławski came to America, settled in San Francisco, California, worked in the business of importing books and periodicals from the Soviet Union, and became the owner and manager of the Russian bookstore, Globus, for 34 years (from 1984–2018). Ahrens-Puławski describes the challenges she faced in learning how to run a business, adopting to new computer technologies, and adapting to changes in the Soviet-Russian book trade brought about first by perestroika and later by the information revolution and the internet.